ANALISIS MODEL PELATIHAN PADA LEMBAGA KURSUS DAN PELATIHAN TATA RIAS IFO Jl. LETDA SUJONO KEC. MEDAN TEMBUNG - Shafa, Aliyyah Maahira (Program Studi Pendidikan Luar Sekolah, 2023)
This study aims to determine the training model used at the IFO Makeup Course and Training Institute, Jalan Letda Sujono, Kec. Medan Tembung, North Sumatra, Indonesia. By using a qualitative approach, descriptive methods and data collection techniques include observation, interviews, documentation studies. Based on the results of observations regarding the Training Models and Models used at the IFO Makeup Course and Training Institute, Jalan Letda Sujono, Kec. Medan Tembung, North Sumatra, Indonesia. There are 3 Training Models namely Deductive, Inductive and Classical Models. And after we observed the training model conducted at the IFO Special Institute and Cosmetology Training was a Deductive model because the training at IFO focused on determining training needs, they selected participants with the same characteristics and submitted considerations to all participants. Identification results are used in compiling comprehensive training materials. The results of this identification are very useful because from these results the LKP IFO can make/compile training materials that are comprehensive and not just partial. During the training at LKP IFO, to be precise, the cosmetology training, they had 2 instructors and 1 expert recruited from outside.